Inactivation of extremely halophilic hide-damaging bacteria via low-level direct electric current - BİRBİR, MERAL; BİRBİR, YAŞAR (ELSEVIER, 2006)
The presence of proteolytic and lipolytic extremely halophilic bacteria on brine-cured hides reduces the value of the hide as a raw material for leather manufacturing. Every brine curing raceway that produces hide contains a significant number of extremely halophilic bacteria that contaminate almost every hide. The usual brine raceway treatments used to control bacteria during curing do not control halophilic bacteria. The antibacterial effects of passing 0.5-A low level, direct electric current for 30 min on different species of protease, lipase, both protease and lipase producing extremely halophilic bacteria, as well as a mixed population of extremely halophilic bacteria, were examined in liquid media containing organic substances and 25% NaCl. Although the antibacterial effects varied with different extremely halophilic bacterial species, the application of current demonstrated an antibacterial effect within 20 min of treatment of all species tested. A mixed culture of extremely halophilic bacteria was killed within 10 min. It has been demonstrated that treatment time as short as 5 min is sufficient for the total inactivation of protease producing extremely halophilic bacteria of 10(7) CFU/mL while lipase or lipase and protease producing extremely halophilic bacteria were inactivated within 20 min. It was also found that the temperature and pH of the test medium increased during treatment. The maximum temperature rise was 9 degrees C, and the pH increased by 4. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: low-level direct electric current; extremely halophilic bacteria; antibacterial activity; QUALITY; METABOLISM; WATER